Dampak Penghargaan Finansial dan Disiplin Atas Kepuasan Kerja Karyawan - Renata, Dafa Angri; Pramadewi, Arwinence; Junaidi, Rahmat (Cv. Syntax Corporation Indonesia, 2024)
Jantra Radja Persada is a firm that specializes in producing and distributing bottled drinking water (AMDK). It is situated in Tembilahan City, Indragiri Hilir Regency, Riau Province, Indonesia. The research was carried out at CV. Jantra Radja Persada Tembilahan located on Ahmad Yani Street. The objective of this study is to ascertain the impact of financial contentment and work discipline on employee satisfaction with their employment. This research is of a quantitative nature. The study included a population of 36 employees from CV firm, Jantra Radja Persada, located in Tembilahan, Riau Province. The sample used in this study consisted of the complete population, specifically 36 individuals. The investigation employed a saturation sampling strategy. This study employs multiple linear regression analysis with the utilization of SPSS version 25 software. The findings of this study indicate that financial remuneration has a favorable and substantial impact on employee job satisfaction. Additionally, work discipline also has a positive and significant influence on employee job satisfaction. Moreover, the variables of financial reward and work discipline collectively exert a positive and significant effect on employee job satisfaction. Based on this research, it can be inferred that both financial funding and work discipline exert a favorable and substantial impact on employee job satisfaction at CV. Jantra Radja Persada Tembilahan, located in Riau Province. These findings demonstrate the significance of efficient human resource management in enhancing employee work satisfaction. This research suggests that organizations should prioritize financial savings measures and promote strong work discipline in order to enhance employee job satisfaction. By implementing this approach, firms can provide a conducive work atmosphere that fosters employee motivation and enhances their performance.